Monitoring extracellular pH, oxygen, and dopamine during reward delivery in the striatum of primates - Ariansen, Jennifer L. (Frontiers Media S.A., 2012)
Dopamine projections that extend from the ventral tegmental area to the striatum have been implicated in the biological basis for behaviors associated with reward and addiction. Until recently, it has been difficult to evaluate the complex balance of energy utilization and neural activity in the striatum. Many techniques such as electrophysiology, functional magnetic resonance imaging (fMRI), and fast-scan cyclic voltammetry have been employed to monitor these neurochemical and neurophysiological changes. In this brain region, physiological responses to cues and rewards cause local, transient pH changes. Oxygen and pH are coupled in the brain through a complex system of blood flow and metabolism as a result of transient neural activity. Indeed, this balance is at the heart of imaging studies such as fMRI. To this end, we measured pH and O(2) changes with fast-scan cyclic voltammetry in the striatum as indices of changes in metabolism and blood flow in vivo in three Macaca mulatta monkeys during reward-based behaviors. Specifically, the animals were presented with Pavlovian conditioned cues that predicted different probabilities of liquid reward. They also received free reward without predictive cues. The primary detected change consisted of pH shifts in the striatal extracellular environment following the reward predicting cues or the free reward. We observed three types of cue responses that consisted of purely basic pH shifts, basic pH shifts followed by acidic pH shifts, and purely acidic pH shifts. These responses increased with reward probability, but were not significantly different from each other. The pH changes were accompanied by increases in extracellular O(2). The changes in pH and extracellular O(2) are consistent with current theories of metabolism and blood flow. However, they were of sufficient magnitude that they masked dopamine changes in the majority of cases. The findings suggest a role of these chemical responses in neuronal reward processing.